Dzieje niemieckojęzycznych przekładów i wydań Biblii od IV do XVI stulecia - Wawrzynek, Karin; Sebesta, Jadwiga (Studia Europaea Gnesnensia, 2011)
The culture of German language owes much to the dynamic development and permanent work on translation of the Bible. The national character of the translations, which accompanied the waves of evangelization also matched the phases of the devel-opment of German language, and had an accordingly huge influence on the literary works of the German speaking territories. Since the gothic translations a continual tendency may be observed that the Bible has to reflect, as precisely and accurately as possible, the mentality and notions of the inhabitants of the German lands. The many sections of Christianity which existed in Europe, decided about the diversity of transla-tions and interpretations of the Holy Scripture.